(untitled) (Research, Society and Development, 2020)
Exogenous intoxication is characterized by the interaction of chemical substances with the living organism. Annually 1.5 to 3% of the population is intoxicated making the disease a public / collective health issue. Quantify and analyze reported cases of drug poisoning in Brazil. This was a documentary, retrospective, descriptive research with a quantitative approach. The notified cases of drug intoxication were collected from the Department of Informatics of the Unified Health System (DATASUS) having the variables studied: region, year, sex, circumstance, final classification and evolution. 224,901 cases of drug poisoning were studied in the aforementioned period, and through these cases it was found that there was a gradual increase in the number of notifications over the years studied, 28% in 2017. Of the notified cases 51% belonged the southeast region. The female sex was predominant, accounting for 70% of cases. The most reported circumstance of intoxication was suicide attempt (59%) and the final predominant classification was confirmed intoxication (68%). Considering the evolution of reported cases, most of them evolved to cure without sequelae (83%). The investigation made it possible to know the epidemiological profile of notified cases of drug poisoning in Brazil. From these findings, it is concluded that there is a need to implement policies to minimize the risks to human health due to the use of medicines. In addition, it is also important to incorporate the standard as a basic work tool to generate accurate and updated data in the national databases. Such factors demonstrate the importance of implementing a Toxicological Information and Assistance Center (CIAT) throughout Brazil, as well as Hospital Epidemiology Centers (NEH) to better monitor the profile of drug poisoning.